2003
DOI: 10.1161/01.str.0000049767.14156.2c
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Caregiver Consequences of Early Supported Discharge for Stroke Patients

Abstract: Background and Purpose-Early supported discharge (ESD) for stroke has been shown to yield outcomes similar to or better than those of conventional care, but there is less information on the impact on costs and on the caregiver. The purpose of this study is to estimate the costs associated with an ESD program compared with those of usual care. Methods-We conducted a randomized controlled trial of stroke patients who required rehabilitation services and who had a caregiver at home. Results-Acute-care costs incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 43 publications
0
104
0
Order By: Relevance
“…After a major event, patients with mild disability underwent one year of rehabilitation at a cost of $2176. 34 For those with permanent disability, we estimated an average yearly cost of $33 532 for care. 35 Costs are summarized in online Appendix 2 (www.cmaj.ca/cgi/content/full/174 /13/1847/DC2).…”
Section: Resultsmentioning
confidence: 99%
“…After a major event, patients with mild disability underwent one year of rehabilitation at a cost of $2176. 34 For those with permanent disability, we estimated an average yearly cost of $33 532 for care. 35 Costs are summarized in online Appendix 2 (www.cmaj.ca/cgi/content/full/174 /13/1847/DC2).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported significantly heightened stress 2 and poorer mental health in carers receiving Early Supported Discharge. Other studies have shown no adverse impact on the subjective well-being 4 of carers and reduced caregiver burden 7 for carers of stroke patients receiving Early Supported Discharge compared with conventional services. However, none of the aforementioned studies used qualitative methodology to allow patients and carers to describe their experiences in their own words.…”
Section: Introductionmentioning
confidence: 90%
“…Ten studies estimating the cost of stroke (12,(15)(16)(17)(18)(19)(20)(21)(22)(23), of which three were Canadian studies and two were European reviews, were identified and are summarized in Table 2. Canada: Based on various public and private sources, the direct cost of stroke in Ontario was calculated to be at 2.7% of the total direct health care expenditures of Ontario (15).…”
Section: Strokementioning
confidence: 99%
“…In a randomized controlled trial (22), a tailored home intervention was shown to significantly reduce caregiver time and save money compared with usual care following discharge of stroke patients requiring rehabilitation service and who had a caregiver at home. In this study, the three-month direct medical cost following discharge was calculated to be $9,017 per patient in the intervention group and $12,818 in the usual care group.…”
Section: Strokementioning
confidence: 99%